TELAAH NILAI-NILAI KE-NU-AN DALAM MENYIKAPI PRAKTIK POLITIK PARTAI KEADILAN SEJAHTERA (PKS) - Cahyono, Agus; Teguh, Teguh; Khamami, Akhmad Rizqon; Hosaini, Hosaini (STKIP Pesisir Selatan, 2025)
This study aims to critically examine the values ​​of NU in responding to the political practices of the Prosperous Justice Party (PKS) which represents an Islamic political model based on the tarbiyah movement. The focus of this study is based on the differences in the characteristics of ideology and Islamic approaches between Nahdlatul Ulama (NU) which is moderate and based on the Ahlussunnah wal Jama'ah tradition and PKS which tends to be scripturalist and ideological. This study uses the methodSystematic Literature Review (SLR)by reviewing literature from various national and international scientific journals in the period 2015–2025. The literature was analyzed through a process of identification, selection, and synthesis to gain a deep understanding of NU's response and attitude towards PKS's political style. The results of the study show that NU values ​​such as tawassuth (moderate), tasamuh (tolerant), tawazun (balanced), and i'tidal (fair) encourage a critical but non-confrontational attitude towards identity politics and political pragmatism carried out by PKS. NU's attitude tends to prioritize national ethics and the welfare of the people rather than the dominance of certain political ideologies. In conclusion, NU values ​​function as a balancer in the contestation of Islamic politics and offer an inclusive and contextual approach in dealing with the dynamics of religious politics in Indonesia.